Research on the Influence of the Circumferential Backlash on the Gear Meshing Transmission Precision of Small Steering Gears - Chen Xuan; Zhang Liyong; Zhang Hanlin; Zhang Yu; Jiang Yehu; Li Chengyu; Yuan Fengxia (Jixie chuandong)
In order to study the factors affecting the transmission performance of the steering gear used in agricultural intelligent cars, a small steering gear model is established by RecurDyn. Within the allowable range of the circumferential backlash of each gear group, the changes of different circumferential backlashes are obtained by adjusting the tooth thickness of the gear group. The simulation of acceleration, deceleration and forward and reverse rotation of the steering gear model shows that when the circumferential backlash is 0.130 mm, the accuracy of the output gear 8 of the steering gear is relatively high and the return error is small. This research provides a basis for solving the driving accuracy problem of intelligent cars.